16. Safety and effects on motor cortex of closely repeated cathodal transcranial direct current stimulations (C-tDCS). Issue 12 (December 2017) - Uncini, A.; Zappasodi, F.; Musumeci, G.; Navarra, R.; Caulo, M.; Di Lazzaro, V.
Abstract : To assess safety and effects of five C-tDCS (charge density 342, 857 C/m 2 ) delivered at increasing time intervals in 25 h. Safety was defined as absence of serious adverse events and by magnetic resonance imaging and spectroscopy. Effects on motor cortex excitability were evaluated by motor evoked potential (MEP) amplitudes. Inter-individual MEP variability was calculated by the SEM at baseline and subjects were classified on the basis of the ratio between normalized MEPs after the first stimulation compared to baseline. Thirty-two healthy subjects were enrolled. No serious adverse events occurred. Magnetic resonance imaging and spectroscopy did not show structural and biochemical alterations. Only 56% of subjects responded to cathodal-tDCS with the expected reduction of MEP amplitude, 25% were non-responders and 19% opposite responders. In responders, MEP suppression was 32% one hour after the first cathodal-tDC, 21% three hours after the second, no longer present four hours after the third and 12 h after the fourth cathodal-tDCS. Loss of effect was due to the increasing interval between C-tDCS and not to intervening homeostatic plasticity. Five C-tDCS in 25 h are safe. Interindividual variability on motor cortex excitability and effect duration limited to three hours should be considered in planning therapeutic trials utilizing repeated C-tDCS.